Unveiling healthy carriers and subclinical infections among household contacts of leprosy patients who play potential roles in the disease chain of transmission - Sérgio Araújo; Janaína Lobato; Érica de Melo Reis; Dulcinéa Oliveira Bernardes Souza; Maria Aparecida Gonçalves; Adeilson Vieira Costa; Luiz Ricardo Goulart; Isabela Maria Bernardes Goulart (Memorias do Instituto Oswaldo Cruz, 2012)
Leprosy transmission still occurs despite the availability of highly effective treatment. The next step towards successfully eliminating leprosy is interrupting the chain of transmission of the aetiological agent, Mycobacterium leprae. In this investigation, we provide evidence that household contacts (HHCs) of leprosy patients might not only have subclinical infections, but may also be actively involved in bacilli transmission. We studied 444 patients and 1,352 contacts using anti-phenolic glycolipid-I (PGL-I) serology and quantitative polymerase chain reaction (qPCR) to test for M. leprae DNA in nasal swabs. We classified the patients according to the clinical form of their disease and the contacts according to the characteristics of their index case. Overall, 63.3% and 34.2% of patients tested positive by ELISA and PCR, respectively. For HHCs, 13.3% had a positive ELISA test result and 4.7% had a positive PCR test result. The presence of circulating anti-PGL-I among healthy contacts (with or without a positive PCR test result from nasal swabs) was considered to indicate a subclinical infection. DNA detected in nasal swabs also indicates the presence of bacilli at the site of transmission and bacterial entrance. We suggest that the concomitant use of both assays may allow us to detect subclinical infection in HHCs and to identify possible bacilli carriers who may transmit and disseminate disease in endemic regions. Chemoprophylaxis of these contacts is suggested.